Phloem loading in rice leaves depends strongly on the apoplastic pathway. (24th February 2021) - Wang, Gaopeng; Wu, Yue; Ma, Li; Lin, Yan; Hu, Yuxiang; Li, Mengzhu; Li, Weiwei; Ding, Yanfeng; Chen, Lin
Abstract : A major fraction of sugars that are exported from rice leaves are loaded into the phloem via the sucrose transporter-mediated apoplastic pathway. Abstract: Phloem loading is the first step in sucrose transport from source leaves to sink organs. The phloem loading strategy in rice remains unclear. To determine the potential phloem loading mechanism in rice, yeast invertase ( INV ) was overexpressed by a 35S promoter specifically in the cell wall to block sugar transmembrane loading in rice. The transgenic lines exhibited obvious phloem loading suppression characteristics accompanied by the accumulation of sucrose and starch, restricted vegetative growth and decreased grain yields. The decreased sucrose exudation rate with p-chloromercuribenzenesulfonic acid (PCMBS) treatment also indicated that rice actively transported sucrose into the phloem. OsSUT1 ( SUCROSE TRANSPORTER 1 ) showed the highest mRNA levels of the plasma membrane-localized OsSUT s in source leaves. Cross sections of the OsSUT::GUS transgenic plants showed that the expression of OsSUT1 and OsSUT5 occurred in the phloem companion cells. Rice ossut1 mutants showed reduced growth and grain yield, supporting the hypothesis of OsSUT1 acting in phloem loading. Based on these results, we conclude that apoplastic phloem loading plays a major role in the export of sugar from rice leaves.